2014
DOI: 10.1254/jphs.14r06cr
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2C Receptor as a Superhero: Diversities and Talents in the RNA Universe for Editing, Variant, Small RNA and Other Expected Functional RNAs

Abstract: The serotonin 2C receptor subtype (5-HT2C) seems to have various physiological roles in addition to the function of the receptor. The serotonin receptors are classified into many subtypes (1), especially more than 10 splicing variants have been reported for the 5-HT4 subtype (1, 2), which has been recently reported to be involved in the circadian clock (3, 4). Among the various serotonin receptor subtypes, 5-HT2C is especially interesting. The history of studies on 5-HT2C can also convey its distinct personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…We also found that HET is involved serotonin 2C receptor (5-HT2CR) function and the mRNA expression [2] as well as antidepressants [2][3][4]. 5-HT2CR has been reportedly suggested the concerning with the neuronal development [5][6][7]. It has been also reported that HET-or typical antidepressants-treatment strongly enhanced BNIP-3 mRNA expression in cloned neuronal cells by experiments starting from the results of DNA array [8].…”
Section: Introductionmentioning
confidence: 93%
“…We also found that HET is involved serotonin 2C receptor (5-HT2CR) function and the mRNA expression [2] as well as antidepressants [2][3][4]. 5-HT2CR has been reportedly suggested the concerning with the neuronal development [5][6][7]. It has been also reported that HET-or typical antidepressants-treatment strongly enhanced BNIP-3 mRNA expression in cloned neuronal cells by experiments starting from the results of DNA array [8].…”
Section: Introductionmentioning
confidence: 93%
“…To date, ADAR1, ADAR2, and ADAR3 have been identified, whereas target RNAs of ADAR3 have not been found (Nishikura, 2010). RNA is an energetically unstable molecule, thus it is considered that RNA is edited in order to respond rapidly to a change in the surrounding environment (Tohda, 2014). Most RNA editing occurs in 3 or 5 untranslated regions and this regulates gene expression.…”
Section: Rna Editing Of 5-ht 2c R Mrnamentioning
confidence: 99%